Affinity Chromatography: A Powerful Tool in Drug Discovery for Investigating Ligand/membrane Protein Interactions. Issue 3 (3rd July 2021) - Lecas, Lucile; Dugas, Vincent; Demesmay, Claire
ABSTRACT: Affinity chromatography is an often overlooked chromatographic technique regarding receptor/ligand studies. Indeed, biologists have a tendency to focus on more recent biophysical techniques such as NMR or surface plasmon resonance methods, among others. However, in order to face challenges related to the use of membrane proteins in drug discovery, alternative and/or complementary methods are welcome. In this frame, chromatographic methods, through the affinity mode, bring new perspectives due to their relative simplicity and the great diversity of information that they can provide. Affinity chromatography methods rely on the immobilization of targets on the stationary phase and this step is crucial when dealing with membrane proteins. Different immobilization strategies with their own specificities (surface density, nonspecific interaction, complex surface chemistry of the taking or release step) were developed allowing to encompass a wide range of applications: from ligand-ranking (synthetic compounds of medium to high affinity) to fragment screening (small compounds of weak affinity), adsorption, distribution, metabolism, and excretion studies or identification of active components from natural extracts.